2009
DOI: 10.2337/db09-0567
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans as Model for the Study of High Glucose– Mediated Life Span Reduction

Abstract: OBJECTIVEEstablishing Caenorhabditis elegans as a model for glucose toxicity–mediated life span reduction.RESEARCH DESIGN AND METHODSC. elegans were maintained to achieve glucose concentrations resembling the hyperglycemic conditions in diabetic patients. The effects of high glucose on life span, glyoxalase-1 activity, advanced glycation end products (AGEs), and reactive oxygen species (ROS) formation and on mitochondrial function were studied.RESULTSHigh glucose conditions reduced mean life span from 18.5 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
240
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(291 citation statements)
references
References 17 publications
34
240
2
1
Order By: Relevance
“…As the animals aged, exposure to glucose concentrations below the toxicity threshold caused no change in pumping rates, whereas concentrations at (250 mm) or above (333 mm) the threshold caused a slight reduction in pumping rates (20% decrease compared to control; Figure 1C and data not shown). Because glucose stress leads to shortened life span in C. elegans (Schulz et al 2007;Lee et al 2009;Schlotterer et al 2009), this pumping decline may be a general symptom of sick and dying animals, consistent with our own observations on the effects of glucose toxicity on life span.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…As the animals aged, exposure to glucose concentrations below the toxicity threshold caused no change in pumping rates, whereas concentrations at (250 mm) or above (333 mm) the threshold caused a slight reduction in pumping rates (20% decrease compared to control; Figure 1C and data not shown). Because glucose stress leads to shortened life span in C. elegans (Schulz et al 2007;Lee et al 2009;Schlotterer et al 2009), this pumping decline may be a general symptom of sick and dying animals, consistent with our own observations on the effects of glucose toxicity on life span.…”
Section: Resultssupporting
confidence: 88%
“…In addition, the frequency of infertility, developmental defects, pregnancy complications, and perinatal mortality is higher in obese and diabetic patients (reviewed in Tsoi et al 2010;Vimaleswaran and Loos 2010). Like mammals, C. elegans is subject to glucose toxicity, as high levels of glucose lead to reductions in fertility (Lu and Goetsch 1993;Lee et al 2009) (Figure 1) and life span (Schulz et al 2007;Lee et al 2009;Schlotterer et al 2009). The conservation of glucose-responsive pathways, including the insulin-like signaling pathway and the hexosamine signaling pathway, coupled with the ability to control diet and genetic background, make C. elegans an excellent model system for studying the glucose stress response and the genes that determine the threshold for glucose toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ceramides are also implicated in ischemic responses, the functional role ceramides have in anoxia survival is not well understood (Argraves et al 2011;Novgorodov and Gudz 2011). Of interest are the recent findings that ceramides are associated with impaired insulin action and the incidence of type 2 diabetes (Galadari et al 2013;Lopez et al 2013;Larsen and Tennagels 2014;Turpin et al 2014).Several studies have shown that a high glucose diet impacts the metabolism, development, and stress responses of C. elegans (Lee et al 2009;Schlotterer et al 2009;Choi 2011;Mondoux et al 2011) and that pathways and cellular processes involving glucose metabolism are conserved in metazoans (Berninsone 2006;Forsythe et al 2006;Hashmi et al 2013;Kitaoka et al 2013). Here, we use C. elegans to examine the impact a glucose diet has on oxygen deprivation responses and gene expression.…”
mentioning
confidence: 99%
“…This has been shown in endothelial cells transfected to overexpress GLO1 which accumulate less MGO and subsequently contain less AGEs [62,83]. Nematode worms engineered to overexpress GLO1 also contain fewer MGO-derived AGE adducts, and the worms demonstrate increased life-span [52,61]. More recently it has been shown that overexpression of GLO1 in diabetic rats is significantly protective against key retinopathy lesions including Müller glia damage and formation of acellular capillaries [91].…”
Section: Natural Defence Against Age/alesmentioning
confidence: 95%